Perancangan Sistem Penyiraman Tanaman Otomatis Berbasis TDR CN101A Dengan Tegangan 12v Di Kebun Politeknik Negeri Ketapang - Allkadri, Syarif Ishak; Radwitya, Erick (Electrical Network Systems and Sources, 2024)
ABSTRACT Effective and efficient watering of plants is very important in maintaining the success of plant growth. In this research, an automatic plant watering system was developed using TDR CN101A with 12V voltage in the Ketapang State Polytechnic garden. The purpose of this research is to design and implement an automatic watering system that can adjust the watering schedule without the presence of humans directly. This research uses TDR CN101A as a digital time control module to adjust the watering schedule. This system is supported by a 12V water pump that will supply water to the plants according to a predetermined schedule. In addition, a 12V relay is used to control the water pump using a signal from the TDR CN101A. This system is designed to overcome the problem of managing watering schedules and reduce the need for direct human intervention. By using the TDR CN101A, the user can adjust the watering schedule according to the needs of the plants. In addition, users can also easily change the schedule according to changes in plant conditions. This research was conducted at the Ketapang State Polytechnic garden with the aim of implementing an efficient and practical automatic watering system. Observational data and test results will be analyzed to evaluate the performance of the automatic watering system and its effectiveness in maintaining soil moisture suitable for plant growth. It is hoped that the results of this research can contribute to the development of a more efficient automatic watering system that can be implemented on a wider scale. This system can be used as a basis for developing more sophisticated and efficient automatic plant watering solutions in the future. Keywords: Automatic watering system, TDR CN101A, 12V water pump, Ketapang State Polytechnic garden.